Impact of Online Banking on Customers Satisfactions: Exploring the impact of online banking on customer satisfaction and banking operations (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Online banking constitutes an electronic alternative network of payments and benefit of services. The need of creation of electronic alternative channels has been distinguished well in advance by the foreign banking organizations, which relied mainly on the outburst that was observed in the use of internet. The benefits are many, both for the customers and for the banks. The banks that are activated in the Internet are susceptible mainly to the systematic, law part and to the reputational risk and the customers of the electronic banking channel are puzzled concerning to the subject of safety of their transactions and personal data. The aim of this report is, not only to analyze the meaning of electronic banking and to present all the alternative providing banking service networks, but also to focus on the advantages and on the risks that the growth of electronic banking has brought about.The rapid growth of Information Technology (IT) has tremendously changed the way banking is done worldwide. For obtaining service the customers need not to visit Brick and mortars structure of the Bank. All the services of the Bank can be utilized by alternate channels sitting at any location away from Bank. The influence of IT on banking enables the customer to get all major operations/decisions with regard to deposits, withdrawals, and investments by just clicking of a mouse on a computer or at an Automatic Teller Machine (ATM) or mobile. Direct Banking channels or alternate banking channels can be utilized by banks for acquiring, tracking and serving customers through multiple channels. An entire range of services including account opening, fund transfers third party transfers, utility payments can be done through using direct banking channels.